Public policy supporting innovation for sustainable development - Brás, Gonçalo Rodrigues; Robaina, Margarita (Frontiers in Sustainability, 2025)
What are the market priorities driving public funding for innovation? Do they reflect the priorities/interests of wider society or the sustainable development agenda? The market’s failure to deliver desirable innovation outcomes aligned with sustainable development must be addressed by public policy in the scope of responsible (and research) innovation principles. Public funding for innovation must support sustainable development to the benefit of society as a whole. Given the urgent need for action, the article proposes some innovative instruments with a view to achieving sound sustainable development.